Síndrome de vena cava superior: una serie de casos consecutivos en pacientes internados en un hospital terciario universitario - Ferraris, Augusto; Jabif, Fernado; Pollán, Javier (Revista del Hospital Italiano de Buenos Aires, 2022)
Introduction: superior vena cava syndrome results from an obstruction of blood flow through this vessel. Currently, almost all cases are associated with malignancies. There are controversies about the optimal management of this syndrome. Endovascular therapies are considered the first-line therapy.Material and methods: we collected clinical, laboratory and pharmacological data from patients admitted at the Hospital Italiano de Buenos Aires, between January 1st and November 1st 2021 with a diagnosis o superior vein cava syndrome. Baseline characteristics, treatment strategies and clinical outcomes were recorded.Results: a total of five patients were included in the present study. All cases were malignancy-related. Most of the patientsdeveloped moderate symptoms. Four out of five patients were treated with endovascular therapies and two patients died during hospitalization.Discussion: controversies regarding optimal management of the superior vena cava syndrome remain. Future research should focus on identifying those patients who are most likely to benefit from endovascular, anticoagulant or antiplatelet therapeutic strategies.